Measures of oxidative state are primarily driven by extrinsic factors in a long-distance migrant. (16th January 2019) - Bodey, Thomas W.; Cleasby, Ian R.; Blount, Jonathan D.; Vigfusdottir, Freydis; Mackie, Kerry; Bearhop, Stuart
Abstract : Oxidative stress is a likely consequence of hard physical exertion and thus a potential mediator of life-history trade-offs in migratory animals. However, little is known about the relative importance of intrinsic and extrinsic stressors on the oxidative state of individuals in wild populations. We quantified the relationships between air temperature, sex, body condition and three markers of oxidative state (malondialdehyde, superoxide dismutase and total antioxidant capacity) across hundreds of individuals of a long-distance migrant (the brent goose Branta bernicla hrota ) during wintering and spring staging. We found that air temperature and migratory stage were the strongest predictors of oxidative state. This emphasizes the importance of extrinsic factors in regulating the oxidative state of migrating birds, with differential effects across the migration. The significance of abiotic effects demonstrates an additional mechanism by which changing climates may affect migratory costs.